THE DEVELOPMENT AND USE OF STANDARD ERGONOMIC PRODUCTS INCREASES PRODUCTIVITY - Gempur Santoso, (Jurnal Cakrawala Ilmiah, 2023)
Workers need safety and comfort when using equipment at work. Every human being really does not want accidents in his life. However, not every human being is necessarily able to make or choose ergonomic products, one of which is to result in safety, increased comfort and productivity. Therefore, in order for this to be achieved, it must be designed ergonomically. In scientific writing, the method used is descriptive from the study of literature. The conclusion is that the development of ergonomic products since before the century AD until now the application of ergonomics is growing; with ergonomic products and doing work that is healthy, safe, comfortable or easy, does not cause harm, productivity will improve (increase).